Indian Baghdadi Jews in Literature: A Murder, a Prostitute, and a Drug Dealer - Lodh, Sayan (Women in Judaism)

(untitled) (Women in Judaism, Inc., 2023)
The article examines the depiction of female Baghdadi Jewish characters in three works: Gay Courter’s English novel Flowers in the Blood (2002), Saadat Hasan Manto’s Urdu short story Mozelle (1951), and Sharadindu Bandyopadhyay’s Bengali story Makorshar Rosh (1933). It explores a murder case from Calcutta Jewry through the eyes of Courter’s protagonist Dinah Sassoon, a prevalent vice among the poorer Baghdadis through the character of a Jewish prostitute, Mozelle, and the role of Baghdadis in drug-trafficking through the character of Rebecca Light. The 21st century novel offers a nuanced understanding of characters, while the earlier short stories reflect their authors’ stereotypical understanding of their contemporary society.